2021
DOI: 10.1017/sjp.2021.30
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia as a Heterogeneous Condition: Subgroups of Patients Based on Physical Symptoms and Cognitive-Affective Variables Related to Pain

Abstract: Fibromyalgia (FM) is a chronic syndrome characterized by heterogeneous clinical manifestations, and knowing this variability can help to develop tailored treatments. To understand better the heterogeneity of FM the present cross-sectional study analyzed the role of several physical symptoms (pain, fatigue and poor sleep quality) and cognitive-affective variables related to pain (pain catastrophizing, pain vigilance, self-efficacy in pain management, and pain acceptance) in the configuration of clinical profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Several clinical aspects (pain, fatigue, restful sleep, emotional distress, difficulty in daily functioning, and coping with the disease), representative of physical/ psychological experience of FM (see Martínez et al, 2021) and consonant with the questionnaire items, were selected from the ED. The reliability of this set of variables was acceptable (α = .72) in all periods of the day.…”
Section: Correlational Data Between Ed Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical aspects (pain, fatigue, restful sleep, emotional distress, difficulty in daily functioning, and coping with the disease), representative of physical/ psychological experience of FM (see Martínez et al, 2021) and consonant with the questionnaire items, were selected from the ED. The reliability of this set of variables was acceptable (α = .72) in all periods of the day.…”
Section: Correlational Data Between Ed Measuresmentioning
confidence: 99%
“…FM patients complain of poor sleep quality, a greater number of awakenings and the presence of a fragmented sleep, with a greater proportion of phases N1 and N2 of NREM sleep and reduction of slow wave sleep (Díaz-Piedra et al, 2015). Nonrestorative sleep is related to higher levels of pain, emotional distress and lower self-efficacy and daily functioning (Andrade et al, 2020;Choy, 2015;Miró et al, 2011a), being a key aspect in the establishment of subgroups of FM patients (Martínez et al, 2021). Also, it has been shown that cognitive-behavioral therapy for insomnia (CBT-I) improves several of these aspects such as cognitive function (Miró et al, 2011b), daily functioning and psychological well-being , and that the combined CBT for insomnia and pain (CBT-IP) produces positive changes in pain-related variables (Lami et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…This plethora of manifestations suggests complex interactions explaining the heterogeneity in the clinical presentation observed in people with FMS. In fact, there is evidence suggesting the presence of different subgroups of women with FMS combining higher or lower sensitivity, and more or less stress [7][8][9][10]. These studies used pain-and disabilityrelated, cognitive, or psychological aspects to identify subgroups of patients with FMS using cluster analysis.…”
Section: Introductionmentioning
confidence: 99%
“…These studies used pain-and disabilityrelated, cognitive, or psychological aspects to identify subgroups of patients with FMS using cluster analysis. Additionally, considering that one of the most common features of FMS is hypersensitivity to pressure pain (expressed as a decreased pressure pain threshold), these previous studies did not include this psychophysiological outcome when evaluating altered nociceptive pain processing in their analyses [7][8][9][10]. The application of cluster analysis is able to identify subgroups of individuals based on common variables; however, it does not identify complex interactions or mediating effects between the variables.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the role that psychological protective factors (i.e., general self-efficacy) play in how people with chronic pain perceive the extension of that pain undergone limited evaluation [ 20 , 21 ]. Resilience, a psychological protective factor, has been associated with widespread pain sensitivity in participants with shoulder pain [ 8 ].Expectations of recovery, optimism, pain acceptance, and pain self-efficacy are involved in widespread pain conditions such as fibromyalgia [ 22 25 ]. To our knowledge, no observational studies have analysed the potential association between these psychological protective factors and digital pain extent in chronic musculoskeletal pain.…”
Section: Introductionmentioning
confidence: 99%